(untitled) (Jurnal Manajemen dan Organisasi, 2016)
Every investment option are risky because of uncertainty. Each investment instruments have different risk levels. Measurement of risk impact depends on the type of Investment. "Do not put all your eggs into one basket" is frequently echoed to warning investors as suggestions effort to minimize the risks by investing in diversified portfolio to avoid losses. The sharpe method and Jensen method are the main analytical tools to analize Equity Fund Performance. The research are analyzing many of mutual fund such as TRIM Kapital mutual fund, Firtis Ekuitas mutual fund, Batavia Dana Saham mutual fund, and Schroder Dana Prestasi mutual fund. The research result gave the rating for the performance of stock mutual funds, which can be help investors and prospective investors in assessing the merits of a mutual fund. The ranking describe the ability of fund managers in managing performance of mutual funds, which the highest ranked have better ability than the other investment managers.